Representações do insólito como tensão: as artesanias de Rowling e Bojunga tecendo olhares dissonantes - Brito, Ana Paula Caixeta (2019)
This study intend to analyze the comprehensive of the unusual and its creation in the literary narratives chosen from theories, concepts, and term analyzes, proposing a broader vision of the unusual event in the narratives, when we relate it to many chances of understanding of the real. To such critical thinking, we will use the novel Corda Bamba, by Lygia Bojunga and the short stories “A Fonte da Sorte”, and “O Conto dos Três Irmãos”, found in the book Os Contos de Beedle, O Bardo, by J.K. Rowling. We also intend to explore the poetic construction of the objects and its relationship with narrative characters, beyond its effects of meaning created in the text from this relationship.